Speech Portrait of a Mentally Unhealthy Character as a Translation Problem - E. A. Barmina; O. G. Skidan (Научный диалог)
The aim of this article is to describe the mechanism of determining the key parameters of the speech portrait of a mentally unhealthy character in a literary text in terms of achieving pragmatic adequacy in translation. The material used for analysis includes the novel ‘Flowers for Algernon’ by Daniel Keyes, the short story ‘Survivor Type’ by Stephen King, and the novel ‘American Psycho’ by Bret Easton Ellis. The authors utilize a proposed algorithm of pretranslation analysis as a tool. It has been established that specific linguistic markers are employed in creating the speech portrait in literary texts, observed through one or multiple parameters. These linguistic markers accurately characterize the existing facts of altered language consciousness in mental disorders. Components of the character’s speech portrait may include verbal aggression (obscene language), metaphors, specific sentence structures, verbalization of grandiosity, etc. The authors conclude that the proposed algorithm, with the application of psycholinguistics data, allows for tracing the peculiarities of selecting expressive means in the original text and identifying relevant markers of the speech portrait of a mentally unhealthy character for subsequent representation of these characteristics as functional dominants in translation. This will help avoid shifts in realizing the character’s image in translation.